A Comparative Study Of Islamic And International Humanitarian Law - Nabiebu, Miebaka (Pinisi Journal of Social Science, 2023)
Human communities have always been marked by conflicts, which came to be controlled by ethical and legal standards that developed along with human civilization. These widely accepted standards were eventually established as contemporary International Humanitarian Law (IHL). Additionally, it is commonly believed that this legislation has developed largely as a result of modern European activities, diminishing any potential contributions from other cultures and ethical traditions to its development and codification. However, it is noteworthy that the principles of jus ad bellum (law governing the use of force) and jus in Bello (content of the law of war) were evident in Islamic literature centuries before modern IHL was codified, with little attention paid to them. Jihad, or Islamic conflict, has been the subject of some existing literature, but the notion of Islamic humanitarian law within the context of IHL has not been thoroughly explored. Therefore, this study aims to fill a gap in the existing literature by reviewing Islamic humanitarian law within the ambit of IHL. This essay argues that Islamic humanitarian law, which regulates the treatment of prisoners of war, is extensive and comparable to the 1949 Geneva Convention's provisions. Additionally, the concepts of Siyar Islamic literature are strikingly similar to those of the Geneva Convention. This research adds to international relations by examining the degree of conformity between the requirements of Islamic Humanitarian Law and Modern IHL with regard to a matter of immediate practical relevance in an era when some regions of the world are suffering armed conflict